Learners’ perceptions of blended learning in technical English classes at the National Institute of Technology - FUJITA, Takuro (ARELE: Annual Review of English Language Education in Japan, 2021)
This study reports on longitudinal practitioner research on technical English classes conducted at the National Institute of Technology. Targeting first-year students, this study examined the learners’ perceptions of blended learning—a combination of web-based training (WBT) and face-to-face classes—based on the framework of exploratory practice. Different types of lessons were conducted throughout the year. In the first semester, the learners took face-to-face classes. They then worked on WBT and reviewed what they had studied. In the second semester, the learners utilized the WBT and prepared for face-to-face classes in advance. Questionnaires and reaction papers were used as data. The results showed that the learners perceived the blended learning lessons as highly effective and flexible. It was also reported that different uses of WBT contributed differently to their learning; the learners felt that using the WBT as review materials enabled them to reduce their anxiety, whereas using the WBT for the preparation of face-to-face classes helped them form a habit of self-study and deepened their learning.